2024
DOI: 10.3390/rs16091580
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Spring-Summer Phenology and Higher Photosynthetic Peak Altered the Seasonal Patterns of Vegetation Productivity in Alpine Ecosystems

Fan Yang,
Chao Liu,
Qianqian Chen
et al.

Abstract: Carbon uptake of vegetation is controlled by phenology and photosynthetic carbon uptake capacity. However, our knowledge of the seasonal responses of vegetation productivity to phenological and physiological changes in alpine ecosystems is still weak. In this study, we quantified the spatio-temporal variations of vegetation phenology and gross primary productivity (GPP) across the source region of the Yellow River (SRYR) by analyzing MODIS-derived vegetation phenology and GPP from 2001 to 2019, and explored ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…POG is usually derived from the time series of vegetation index (VI) and is identified as the time when the smoothed VI curve reaches the maximum [13,14]. Many studies have suggested that POG is an important indicator of terrestrial gross primary production (GPP) variability as it can indicate the timing of the maximum capacity of photosynthesis, i.e., the maximum capacity of CO 2 uptake [15][16][17]. In addition, POG is intimately related to the timing of maximum plant resource availability.…”
Section: Introductionmentioning
confidence: 99%
“…POG is usually derived from the time series of vegetation index (VI) and is identified as the time when the smoothed VI curve reaches the maximum [13,14]. Many studies have suggested that POG is an important indicator of terrestrial gross primary production (GPP) variability as it can indicate the timing of the maximum capacity of photosynthesis, i.e., the maximum capacity of CO 2 uptake [15][16][17]. In addition, POG is intimately related to the timing of maximum plant resource availability.…”
Section: Introductionmentioning
confidence: 99%